2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flow and hemodynamics in the carotid artery using a reduced TE 4D flow spiral phase-contrast MRI

Abstract: In this paper, the accuracy of flow assessment and flow visualization with reduced TE 4D Spiral PC was investigated and good agreement was observed between the spiral and conventional technique. The systolic mean velocity, peak flow and the average flow in CCA and ICA of normal volunteers using 4D spiral PC MRI showed errors less than 10% compared to conventional 4D PC MRI. In addition, the scan time using spiral sequence was 3:31 min which is half of the time using conventional sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In addition, several advanced acceleration methods for the improvement of spatial resolution and/or reduction of total scan time have been successfully explored including k-t BLAST 226 , k-t GRAPPA, k-t SENSE 227 , radial 227 and spiral 228 sampling schemes as well as compressed sensing approaches 229,230 .…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, several advanced acceleration methods for the improvement of spatial resolution and/or reduction of total scan time have been successfully explored including k-t BLAST 226 , k-t GRAPPA, k-t SENSE 227 , radial 227 and spiral 228 sampling schemes as well as compressed sensing approaches 229,230 .…”
Section: Applicationsmentioning
confidence: 99%
“…Spiral k-space trajectories have previously been used for real time and three-directional single-breath-hold 2D flow MRI [114][115][116] and 3D magnetic resonance angiography [117][118][119]. Recently, spiral trajectories have also been used for prospectively-gated 4D flow MRI in the carotid arteries [120] and the aorta (Paper III). Moreover, in Paper IV a retrospectivelygated 4D flow MRI sequence using spiral trajectories was validated for velocity mapping of intra-cardiac velocities.…”
Section: Spiral K-space Trajectoriesmentioning
confidence: 99%
“…Kadbi et al [36,55] showed that the echo time (TE) can be shortened through combination of slice selection gradient with bipolar flow encoding gradient. In the case of 4D UTE PC which involves radial acquisition of k-space and FID sampling, TE is defined as the distance from center of excitation RF pulse to the beginning of the readout gradient.…”
Section: Combining the Bipolar And Slice Select Gradientsmentioning
confidence: 99%
“…In the case of 4D UTE PC which involves radial acquisition of k-space and FID sampling, TE is defined as the distance from center of excitation RF pulse to the beginning of the readout gradient. Figure 50 demonstrates 4D reduced-TE spiral pulse sequence with combined gradients [55]. This sequence has 4 parts, each lasting for one repetition time (TR) and leading to minimum temporal resolution of 4*TR.…”
Section: Combining the Bipolar And Slice Select Gradientsmentioning
confidence: 99%
See 1 more Smart Citation